Climate change, health, and decent work: a call for combined action - Jackson, Bethany; Wright, Nicola (Frontiers in Climate, 2025)
Climate change is the leading crisis of our times exacerbating issues of health and working conditions for labourers. Whilst research has been undertaken looking at the connection between climate and health, health and work, and work and climate, little has been done to assess the intersection of all three concerns. In this perspective, we outline the need for more integrated thinking to address the wide-reaching impacts of climate change and what that means for the achievement of decent work combined with positive health outcomes. We outline current frameworks and ongoing activities seeking to prevent and mitigate risks to health and work within a changing climate and identify the need for a paired path forward on the local (communities, unions, labour organisations) and global (international and national governance) scales to ensure ‘Health-Labour-Climate’ drivers and outcomes are comprehensively addressed.